Being Innovative at Work Through Psychological Contract for Sustainable Human Development - Anggraeni Ade Irma; Derbani Adnane; Kusumastuti Widyahayu Warmmeswara; Prayogi Joni (E3S Web of Conferences)
This research investigated the impact of the psychological contract on employees' innovative behaviour in Small and Medium Enterprises (SMEs) in the tourism industry. The dimensional approach to the dynamic concept of psychological contract and innovative work behaviour was used to demonstrate employee perception. Survey data were collected from 327 employees across 19 SMEs in Central Java, Indonesia. The psychological contract was found to positively affect innovative work behaviour. Perceptions of psychological contract fulfilment have an impact on the increases in innovative work behaviour. These results highlight the importance of examining the dynamic concept of psychological contract on fostering innovative related behaviour on the context of SME's.